The Implementation of the Marine Spatial Plan on the Identity and Rights of the Berakit Orang Suku Laut Community in Bintan Regency, Riau Islands - Haria, Novi Gabriella; Humairah, Jasri Fanny; Iswahyudi; Arieta, Siti (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2024)
This study examine the efforts of the Bintan Regency government to relocate the Sea Nomad or Orang Suku Laut (OSL) community through the Marine Spatial Plan policy, focusing on the positive and negative impacts of this relocation on their rights and cultural identity. Employing a qualitative approach, the research investigates the implementation and impacts of the Marine Spatial Plan using data collected through in-depth interviews, observations and documentations. Findings reveal that the government strategies often rely on persuasive approaches, leveraging the proximity of the OSL’s traditional marine territory to Panglong village. By 2011, resettlement initiatives encompassed 60 families, accompanied by disciplinary administrative measures like record-keeping of ID registration and residence requirement of 5-10 years in Panglong village for housing eligibility. These measures, however, have significantly erroded the cultural identity of the OSL, distancing young generation from their maritime attachment. While the government policy seeks to assimilate the OSL to Malay communities, it poses a threat to the preservation of their authentic marine culture and contradict their right to self-determination as an indigenous people. The study underscores the importance of involving the OSL in Marine Spatial Planning, highlighting their traditional knowledge as a critical resource for achieving inclusive and sustainable development.